2024
DOI: 10.1001/jamahealthforum.2023.5309
|View full text |Cite
|
Sign up to set email alerts
|

Acute Diabetes Complications After Transition to a Value-Based Medication Benefit

J. Franklin Wharam,
Stephanie Argetsinger,
Matthew Lakoma
et al.

Abstract: ImportanceThe association of value-based medication benefits with diabetes health outcomes is uncertain.ObjectiveTo assess the association of a preventive drug list (PDL) value-based medication benefit with acute, preventable diabetes complications.Design, Setting, and ParticipantsThis cohort study used a controlled interrupted time series design and analyzed data from a large, national, commercial health plan from January 1, 2004, through June 30, 2017, for patients with diabetes aged 12 to 64 years enrolled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…These findings from a randomized study of a program that was facilitated by the Value-Based Insurance Design model may help inform the design and evaluation of other programs within the model, which was recently extended by CMS through 2030 . The Value-Based Insurance Design model for prescription drugs has consistently been shown to improve medication adherence and, in some contexts, also improve clinical outcomes and lower total health care spending . More generally, the Value-Based Insurance Design model is intended to improve on traditional cost-sharing mechanisms that have been shown to reduce utilization of both high-value and low-value services …”
Section: Discussionmentioning
confidence: 99%
“…These findings from a randomized study of a program that was facilitated by the Value-Based Insurance Design model may help inform the design and evaluation of other programs within the model, which was recently extended by CMS through 2030 . The Value-Based Insurance Design model for prescription drugs has consistently been shown to improve medication adherence and, in some contexts, also improve clinical outcomes and lower total health care spending . More generally, the Value-Based Insurance Design model is intended to improve on traditional cost-sharing mechanisms that have been shown to reduce utilization of both high-value and low-value services …”
Section: Discussionmentioning
confidence: 99%
“…Such design changes may improve health outcomes in the short term, aligning payer and clinician incentives. A recent study found that a preventive drug list including common cardiometabolic drugs improved health outcomes at 1-year follow-up . Value-based formularies would represent a dramatic departure from the status quo, but they may be necessary to reorient toward value-based care.…”
Section: Overcoming the Challengesmentioning
confidence: 99%